Pengaruh Latihan Intensive Interval Terhadap Daya Tahan Kardiovaskular Pada Atlet Bulu tangkis Tunggal Putra Usia 15 Tahun - Pelamonia, Shandy Pieter; Hananto Puriana , Ramadhany; Wahyono , Muhammad; Dhiaul Haq, Amalia (Jurnal Porkes, 2024)
This research aims to examine whether there is an effect of intensive interval training on cardiovascular endurance in badminton athletes. It is hypothesized that there is a significant effect of intensive interval training on cardiovascular endurance in badminton athletes. This exercise provides an increase in endurance in badminton athletes. The subjects of this study were PB Junior Badminton Club (JRBC) athletes totaling 30 people. The research design is pretest-posttest control group design. This type of research uses quantitative research methods. The data collection method uses the yo-yo test test instrument obtained from the results of doing intensive interval training. Data analysis used to test the hypothesis is the independent t test. The results of the above description can be seen based on the calculation of the results of SPSS 22 data processing, it is found that the sig value. (2 tailed) of 0.003 <0.05, therefore it can be interpreted that there is a difference in the average posttest results of the experimental group and the control group, which means that there is an effect of intensive interval training on cardiovascular endurance.